Violencia y Sociedad - de Andrade Dores, António Pedro (Corporación Universitaria Americana, 2014)
The recent interest in the sociology of violence has arisen at the same time that western societies are being urged to consider the profound social crisis provoked by global financial turmoil. Social changes demand the evolution of sociological practices. The analysis herein proposed, based on the studies of M. Wieviorka, La Violence (2005), and of R. Collins, Violence: A Micro-sociological Theory (2008), concludes that violence is subject to sociological treatments centered on the aggressors, on the struggles for power and on the male gender. There is a lack of connection between practical proposals for violence prevention and the sociology of violence. It is accepted that violence as a subject of study has the potential, as well as the theoretical and social centrality, to promote the debate necessary to bring social theory up to date. This process is more likely to occur in periods of social transformation, when sociology is open to considering subjects that are still taboo in its study of violence, such as the female gender and the state. The rise of the sociology of violence confronts us with a dilemma. We can either collaborate with the construction of a sub-discipline that reproduces the limitations and taboos of current social theory, or we can use the fact that violence has become a “hot topic” as an opportunity to open sociology to themes that are taboo in social theory (such as the vital and harmonious character of the biological aspects of social mechanisms or the normative aspects of social settings).  Resumen El intere?s reciente en la sociologi?a de la violencia ha surgido al mismo tiempo que las sociedades occidentales esta?n requiriendo considerar la profunda crisis social provocada por la agitacio?n financiera global. Los cambios sociales demandan la evolucio?n de las pra?cticas sociolo?gicas. El ana?lisis aqui? expuesto, basado en los estudios de M. Wieviorka, La Violence (2005), and of R. Collins, Violence: A Micro-sociological Theory (2008), concluye que la violencia es objeto de tratamientos sociolo?gicos centrados en los agresores, en las luchas por el poder y en el ge?nero masculino. Hay una falta de conexio?n entre las propuestas pra?cticas para la prevencio?n de la violencia y la sociologi?a de la violencia. Es aceptado que la violencia como objeto de estudio, tiene el potencial, adema?s de la centralidad teo?rica y social, para actualizar la teori?a social. Este proceso ocurre ma?s comu?nmente en peri?odos de transformacio?n social, cuando la sociologi?a esta? abier- ta a considerar objetos de estudio que au?n son tabu?es en su estudio de la violencia, tales como el ge?nero femenino y el Estado. El ascenso de la teori?a de la violencia nos confronta con un dilema. Tenemos la posibilidad de colaborar con la construccio?n de una subdisciplina que reproduce las limitaciones y los tabu?es de la actual teori?a social, o podemos usar el hecho de que la violencia se ha convertido en un “tema candente” como una oportunidad de abrir la sociologi?a a temas que son tabu?es en la teori?a social (tales como el vital y armonioso cara?cter de los aspectos biolo?gicos de los mecanismos sociales o los aspectos normativos de los escenarios sociales.